Biological evaluation of Cow's milk yoghurt fortified with different sources of milk proteins - Youssef, Mervat.S.; Masoud, M.S.; Fayed, A.E. (2007)
The aim of this study was essentially to evaluate the biological quality of cow's milk yoghurt fortified with nil (control) or 1.0% milk protein supplied either from skim milk powder (SMP), sodium caseinate (NaCn), dried whey protein concentrate (DWPC) or by concentrating the milk itself through the ultrafiltration (UF) process to obtain the same protein elevation level. Biologically, the highest true digestibility and net protein utilization were achieved in rats fed on DWPC-yoghurt. However, rats fed on SMP- yoghurt exhibited the highest biological value of protein. Best blood picture, as indicated from white and red blood cells, hemoglobin and hematocrit, was accomplished in rats fed on UF- yo-ghurt followed by those fed on DWPC-one. The profile of blood plasma of rats indicated that DWPC-yoghurt caused the highest level of total protein, albumin (A) and globulin (G). Nevertheless, the highest A/G ratio was occurred due to feed whether on SMP-, UF- or control- yoghurt. Furthermore, rats fed on DWPC-yoghurt gained the best mineral bioavailability as indicated from the highest levels of Ca, P, K, Mg, Cu, Fe and Zn in their blood plasma. The same was valid for UF-yoghurt with respect to P, Mg and Fe and for SMP-yoghurt towards only the K absorption. As a conclusion, UF-technique offers the best possibility for yoghurt quality improvement whether via facilitate the supplementation with WPC or UF-milk retentate to enhance both compositional content and biological quality of yoghurt.
Includes reference.
Summary in Arabic.
Summary in Arabic.
1
Keywords: Evolution -- Biology; Skim milk; Yogurt; food fortification; cultured milk starters; fermentation